Analysis of Well-being and Physical Activity in People with Diabetes Mellitus - Lukšaitė, Agilė; Matulevičiūtė, Eva; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2024)
The term ‘diabetes epidemic’ refers to the rapid and threatening spread of the disease. If inadequately treated, diabetes mellitus (DM) progresses and is associated with extremely dangerous macrovascular (coronary heart disease, infarction, peripheral artery disease) and microvascular (diabetic kidney disease, retinopathy, peripheral neuropathy) complications, and, in extreme cases, is a life-threatening condition [1]. In addition to physical health issues, patients with CD also experience mental health challenges. Aim. To analyse the well-being and physical activity of people with diabetes. Methods. A review of research articles related to diabetes, searched using the following keywords: diabetes, obesity, physical activity, mental health has been conducted. The search for scientific articles on the topic was carried out using PubMed, Clinical Key and Google Scholar electronic scientific databases. The literature review included 26 freely available, full-length articles on the topic written in English between 2018 and 2023. Results. This article discusses the causes of CD and the course and complications of inadequately controlled disease. Changes in patient’s well-being are correlated with depression, anxiety and eating disorders. Physical activity is one of the preventive measures in chronic diseases and is of great benefit for CD patients. The number of obese individuals is increasing with decreasing physical activity. Conclusions. 1. For patients with diabetes, the most important actions are to control their blood glucose levels, exercise regularly and take their prescribed medication. 2. Controlling weight is important to prevent complications of the disease. Diabetes mellitus patients experience not only physical but also psychological difficulties (stress, anxiety, insomnia). Specialists’ advice on diet, physical activity and other lifestyle habits should be followed to avoid complications.
Keywords: diabetes; obesity; physical activity; mental health